2009
DOI: 10.17705/1jais.00203
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Scholarly Influence: Using the Hirsch Indices to Reframe the Discourse

Abstract: This study is part of a program aimed at creating measures enabling a fairer and more complete assessment of a scholar's contribution to a field, thus bringing greater rationality and transparency to the promotion and tenure process. It finds current approaches toward the evaluation of research productivity to be simplistic, atheoretic, and biased toward reinforcing existing reputation and power structures. This study examines the use of the Hirsch family of indices, a robust and theoretically informed metric,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 70 publications
1
51
0
4
Order By: Relevance
“…Future studies can also investigate the question of the diversity of authorship and diversity of publications. Such evidence that we have suggests a predominance of North American authorship (Truex et al, 2009, Keller & Coulthard, 2013. Will this increase or decrease?…”
Section: Cycle Of Strengthening Orthodoxysupporting
confidence: 49%
See 1 more Smart Citation
“…Future studies can also investigate the question of the diversity of authorship and diversity of publications. Such evidence that we have suggests a predominance of North American authorship (Truex et al, 2009, Keller & Coulthard, 2013. Will this increase or decrease?…”
Section: Cycle Of Strengthening Orthodoxysupporting
confidence: 49%
“…IS has been accused of having a North American bias (Gallivan & Benbunan-Fich, 2007) and that North American authors predominate in the top journals (Truex, Cuellar, & Takeda, 2009, Keller & Coulthard, 2013. Indeed, Tourish (2015) has identified that 31 out of the top 33 journals in the rankings produced by the Association of Business Schools in the UK were of US origin.…”
Section: The Potential Effects Of Ranking On Disciplinary Researchmentioning
confidence: 99%
“…First-authorship is granted to the author who has made the largest intellectual contribution to that paper, so we examined only first-authored papers in this study. The fact that we worked with only first-authored papers also explains why we did not use the Hirsch ''H'' Index (Truex et al 2009), which is calculated from a researcher's entire body of publications, when we examined citation rates. The dendrochronologists examined in this study included academic and government researchers from 16 countries (Argentina, Australia, Canada, China, Ethiopia, Germany, Italy, Morocco, New Zealand, Russia, Slovenia, South Africa, Sweden, Switzerland, United Kingdom, and the United States of America) and spanned six continents.…”
Section: Approach and Methodsmentioning
confidence: 99%
“…To avoid the "path dependency" problem (Truex, Cuellar, & Takeda, 2009), respondents could add and rank up to three additional journals for each group. We asked respondents to rank each journal's overall contribution on a seven-point Likerttype scale (0: none, 1: marginal, 2: some, 3: average, good: 4, very good: 5, outstanding: 6), and we aggregated the scores for each journal.…”
Section: Methodsmentioning
confidence: 99%